Features Of The Application Of Game Theory In The Tasks Organizational And Economic Mechanisms Greenhouse Economy - et. al., Sukhrob Umarov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Article Analyzes The Current Organizational And Economic Mechanism For The Functioning Of Greenhouses In The Republic Of Uzbekistan. Using The Methods Of Game Theory, The Problem Of The Optimal Cultivation Of Vegetables And Fruits In The Greenhouse Has Been Solved. The Subject Of The Study Is The Organizational And Economic Mechanism Of The Functioning Of Greenhouses In The Republic Of Uzbekistan. The Purpose Of The Work Is To Identify Problems In The Development Of The Organizational And Economic Mechanism For The Functioning Of Greenhouses In The Republic Of Uzbekistan Using The Theory Of Games. According To The Decree Of The President Of Uzbekistan Dated November 20, 2018 “On Measures To Create Additional Conditions For The Development Of Greenhouse Complexes”, Another 105 Modern Greenhouses Worth 343.3 Million Will Be Created In The Coming Years. The New Complexes, According To The Document, Will Occupy Another 800 Hectares Of Land. A Significant Part Of Them (47 On 405 Hectares) With A Total Value Of More Than 230 Million Dollars Will Be Created In Tashkent And Samarkand. Methods: Methods Of Game Theory, Payment Matrices, Analysis, Comparison. Findings: With The Help Of Game Theory, The Problem Of The Optimal Cultivation Of Vegetables And Fruits In A Greenhouse Has Been Solved. Conclusions: The Use Of Game Theory Can Be Of Great Help In Constructing Production And Financial Plans In A Greenhouse.